2017
DOI: 10.1002/adom.201601000
|View full text |Cite
|
Sign up to set email alerts
|

Chiral and Luminescent TiO2 Nanoparticles

Abstract: In this work, new chiral and luminescent TiO2 nanomaterials are prepared by a single step nonaqueous synthesis. Using circular dichroism spectroscopy it is shown that TiO2 nanoparticles are optically active with almost identical mirror images of one another in the band‐edge region of titanium dioxide. Investigations of the photoluminescence properties reveal a broad shallow trap state emission centered at 440 nm, with a photoluminescence quantum yield of ≈3.5%, which is among the highest reported for TiO2. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
2
29
0
1
Order By: Relevance
“…For the T20VR, the room temperature PL QY is measured to be 5.76%, which is significantly higher than that reported in the literature for TiO 2 nanostructures (QY ≈ 0.05–3.5% or lower) The details of PL QY of our as‐grown and annealed samples are tabulated in Table . Figure a shows the variation of PL QY for the samples grown with various HF concentrations (10 × 10 −3 to 80 × 10 −3 m ) after 3 min vacuum RTA treatment, while Figure b exhibits the change in QY as a function of RTA duration for T20VR.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the T20VR, the room temperature PL QY is measured to be 5.76%, which is significantly higher than that reported in the literature for TiO 2 nanostructures (QY ≈ 0.05–3.5% or lower) The details of PL QY of our as‐grown and annealed samples are tabulated in Table . Figure a shows the variation of PL QY for the samples grown with various HF concentrations (10 × 10 −3 to 80 × 10 −3 m ) after 3 min vacuum RTA treatment, while Figure b exhibits the change in QY as a function of RTA duration for T20VR.…”
Section: Resultssupporting
confidence: 93%
“…This hinders its applicability in living cells and study for nontoxic analogues of these chiral luminescent nanomaterials is of great interest . Recently, Cleary et al reported on the highly luminescent TiO 2 nanoparticles (NPs) with chiral capping ligand having size 30–50 nm with a PL QY up to ≈3.5%. However, the reported PL yields were measured mostly in colloidal solution, where surface functionalization by the solvents may have contribution to the observed PL yield .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Intuitively,c hiral inorganic NCs with chirality transferred from chiral ligands that are bound to their surface are commonly studied, and the species of inorganic materials can vary from metallic nanoparticles (NPs) or clusters to av ariety of semiconductor NCs. Gunko and coauthors [6] reported that diphenylethylenediamine-capped TiO 2 NPs can express chiroptical activities at their band-edge region owing to the overlap of the chiral ligand highest-occupied molecular orbital (HOMOs) with the TiO 2 quantum-dot valence-band states.M ore recently,J . Gunko and coauthors [6] reported that diphenylethylenediamine-capped TiO 2 NPs can express chiroptical activities at their band-edge region owing to the overlap of the chiral ligand highest-occupied molecular orbital (HOMOs) with the TiO 2 quantum-dot valence-band states.M ore recently,J .…”
Section: Chiralinorganicnanocrystals(ncs)asanemergingareahasmentioning
confidence: 99%
“…[5] Among them, chiral metal oxide NPs with ligand induced chirality has triggered tremendous interests for their essential applications in chiral catalysis,b iomaterials,o ptics and understanding of light-matter interactions.T od ate,Y . Gunko and coauthors [6] reported that diphenylethylenediamine-capped TiO 2 NPs can express chiroptical activities at their band-edge region owing to the overlap of the chiral ligand highest-occupied molecular orbital (HOMOs) with the TiO 2 quantum-dot valence-band states.M ore recently,J . Yeom et al [7] synthesized Co 3 O 4 chiromagnetic NPs and their gels that can be used for real-time magnetic field modulation.…”
Section: Chiralinorganicnanocrystals(ncs)asanemergingareahasmentioning
confidence: 99%
“…Arrested growth in a chiral environment, is a common method for synthesis of chiral nanoceramics. In this context, individual chiral ceramic NPs from TiO 2 , [37] tungsten oxide (WO 3−x ) [38] molybdenum oxide (MoO 3−x , MoO 2 ), [39] and zinc oxide (ZnO) [40] and Co 3 O 4 [22b] were reported. The atomic organization of ceramic NPs can be affected by chiral ligands inducing lattice distortion and crystal lattice displacement that may also be referred sometimes to as "chiral footprint."…”
Section: Surface Modificationmentioning
confidence: 99%